Irish migration, all or nothing resolved - Keenan, Jg (Economic & Social Studies, 1981)
Some issues concerning the data are first discussed. Various migration equations for Ireland are estimated and the coefficient differences explained. Despite having a large proportion of explained variation the coefficient estimates in the equations are unstable and are very weak in predicting both the trend and absolute level of the net migration flow. It is concluded that an exogenous estimator of migration flows at the moment gives better predictions than the currently used models which endogenise net migration.
Keywords: Economics; Sociology